Toxigenic Helicobacter pylori induces changes in the gastric mucosal microcirculation in rats - Kalia, N (Copyright 2002 by Gut, 2002)
Background and aims: One of the key components of inflammation is changes in vascular structure and function. This suggests that the microcirculation may be a key target of Helicobacter pylori released factors. It has previously been shown in vivo that pooled H pylori extracts from duodenal ulcer/gastritis patients induce platelet aggregation but no leucocyte activation within rat gastric mucosal microcirculation (GMMC). However, infection with strains associated with ulcer disease as compared with gastritis may exert greater effects on the microcirculation. This study used fluorescent in vivo microscopy to determine the acute effects of extracts of genotypically different H pylori strains on the GMMC. Methods: Three H pylori extracts, with different cagA and VacA toxigenic status, were individually administered to the gastric mucosa of anaesthetised Wistar rats. The mucosal surface was visualised via an incision made in the exteriorised stomach. Fluoroscein isothiocyanate conjugated to bovine serum albumin (FITC-BSA) or acridine orange was used to quantify macromolecular leak (MML) and leucocyte/platelet activity respectively for 120 minutes. Changes in capillary and post-capillary venule (PCV) diameters were also monitored. Results: The cagA(+) VacA toxigenic strain 60190 induced significant and sustained MML by five minutes (p<0.01). Transient and less leakage was observed with its isogenic VacA(−) mutant and other non-toxigenic strains regardless of cagA status. Significant increases in leucocyte adhesion (p<0.05), platelet aggregation (p<0.05), and PCV vasoconstriction (p<0.05) were only observed with the cag A(+) and toxigenic strain. Conclusion: Extracts of H pylori are capable of inducing marked disturbances within the rat GMMC. These disturbances seem to be dependent on the production of an active vacuolating cytotoxin. Varying effects on the GMMC may explain the clinically diverse outcomes associated with genotypically different strains.